Da'wah Management of Islamic Religious Counselors in Pegantenan, Pamekasan during and post Covid-19 Era (MUHARRIK: Jurnal Dakwah dan Sosial, 2021)
Da'wah during the pandemic and new normal era has a role in changing people's behavior and attitudes towards the dangers of Covid-19. The aim of this research is to analyze the management of the preaching of Islamic religious counselors in Pegantenan Pamekasan, East Java using George R. Terry's theory. This study uses a qualitative research approach with a case study type and uses data collection techniques through interviews, documentation and observation. Technique validity of data by triangulation of sources and techniques. Data processing by condensation, data presentation, and conclusions. The results showed: (1) Planning: material, time, target, location, and method. (2) Organizing: First, forming an muslim counselor team: chairman, treasurer, secretary, religious affairs, and mosque councils. The second division of labor tasks: moderator, prayer reader, reader Surah Yasin and Tahlil, the main speaker. (3) Implementation: first, a lecture by providing face-to-face guidance (health protocol) and online. Second, field counseling by providing masks, hand-sanitizers, and spraying disinfectants. (4) Controlling: first by the head of the extension team, assessing the suitability of the implementation of preach with the plan. Second, functional extension agents control material, time, methods, targets, results, impacts, and community complaints. In conclusion, the management of preach by muslim counselor has been carried out well. The research implication is as input and knowledge to preachers about preach management, especially during the pandemic and new normal era.